Creep in Ceramics - Pelleg, Joshua; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on Creep in Ceramics. The book consists of two parts. In part A general knowledge of creep in ceramics is considered, while part B specifies creep in technologically important ceramics, namely creep in oxide ceramics, carnides and nitrides. While covering all relevant information regarding raw materials and characterization of creep in ceramics, the book also summarizes most recent innovations and developments in this field as a result of extensive literature search.
Part A: Basics -- Chapter 1. What is Creep? -- Chapter 2. General Mechanisms of Creep -- Chapter 3. Creep and its Relation to Diffusion -- Chapter 4. Creep in Ceramics -- Chapter 5. Testing Methods for Creep -- Chapter 6. Creep in Nanoceramics -- Chapter 7. Creep Rupture -- Chapter 8. Superplasticity -- Chapter 9. Creep and Recovery -- Chapter 10. Empirical Relations -- Chapter 11. Design for Creep Resistance -- Part B. Creep in Technologically Important Ceramics -- Chapter 12. Creep in Alumina (Al2O3) -- Chapter 13. Creep in Magnesia (MgO) -- Chapter 14. Creep in Zirconia (ZrO2) -- Chapter 15. Creep in Silicon Carbide (SiC) -- Chapter 16. Creep in Boron Carbide (BC) -- Chapter 17. Creep in Silicon Nitride (Si3N4).
Keywords: Materials; Mechanical engineering; Thermodynamics; Geology; Materials Engineering; Mechanical Engineering; Thermodynamics; Geology